Microhabitat selection and distribution of functional feeding groups of mayfly larvae (Ephemeroptera) in lotic karst habitats - Vilenica Marina; Brigić Andreja; Sartori Michel; Mihaljević Zlatko (Knowledge and Management of Aquatic Ecosystems, 2018)
Research examining mayfly ecology in karst streams and rivers has increased in recent years, though microhabitat preferences remain poorly characterized. We examined mayfly assemblage taxonomy, functional feeding groups and microhabitat preferences in two contrasting lotic Dinaric karst catchments, one pristine and one anthropogenically impacted. At monthly intervals over a one-year period, all major microhabitats (i.e. dominated by boulders, cobbles, sand, silt, mosses, or angiosperms) were sampled at sites spanning springs, upper, middle and lower river reaches, and tufa barriers. In both catchments, mayfly species richness was comparable among microhabitats, while mayfly abundance was highest on mosses and lowest on silt. NMDS ordination did not group assemblages according to microhabitat type, which may reflect the greater influence of physical and chemical water properties. In both catchments and all microhabitats, mayfly assemblages were dominated by grazers/scrapers at upstream sites and by detritivores at downstream sites. Active filter feeders were more abundant in microhabitats with silt substrates and lower current velocities. This study demonstrated that certain mayfly species strongly preferred a specific microhabitat type, reflecting their water current preferences and feeding strategies, while other species shifted between microhabitats, likely in search of food resources and shelter. The results emphasize the importance of habitat heterogeneity in supporting diverse communities in karst rivers.